Semi-Refined Carrageenan Attenuates Lipopolysaccharide-Induced Reactive Oxygen Species Production in Peripheral Blood Mononuclear Cells and Cell Membrane Alterations in Leukocytes - Posokhov, Ye. O.; Onishchenko, A.; Chumachenko, T.; Makieieva, N.; Kalashnyk-Vakulenko, Y.; Polikarpova, H.; Novikova, V.; Prokopyuk, V.; Nakonechna, O.; Chumachenko, D.; Tkachenko, V.; Meniailov, I.; et al. (My University, 2021)
Expectedly, incubation with LPS induced ROS generation in PBMCs and decreased the lipid order of cell membranes in leukocytes. E407a alone was found to alter neither ROS production in PBMCs, nor membrane lipid order in leukocytes. Semi-refined carrageenan partially reduced LPS-mediated ROS overproduction in PBMCs and cell membrane alterations in leukocytes.
Keywords: food additive; E407a; 2',7'-dichlorodihydrofluorescein diacetate; fluorescent probes